Analisis Perspektif Guru Terhadap Penerapan Pendekatan Deep Learning dalam Kurikulum Merdeka Di SDN Rajapolah - Sarah Akmalia; Suryana, Dudung; Dwi Febriani, Winarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine teachers' perspectives on the implementation of the deep learning approach in the Independent Curriculum at Rajapolah Elementary School and its impact on student behavior. The study used a descriptive qualitative approach through observations and interviews with the principal, five class teachers, and six students. Data analysis was conducted through data reduction, presentation, and drawing conclusions.The results indicate that teachers' perspectives are very positive. Deep learning influences students' conceptual understanding through three pillars: meaningful, mindful, joyful, and contextual. Benefits include increased participation, motivation, confidence in asking questions and presenting, a safe learning environment free from bullying, and applied learning. Challenges include teachers' uneven understanding, limited time, differences in student characteristics, and difficulties in critical thinking.The impact on student behavior is very positive and significant. Students are more active, often raise their hands, are independent, enjoy group learning, express their opinions, and develop independent and critical character traits. Compared to the 2013 Curriculum, students understand the applied material better, are more active, have a high level of curiosity, and express their opinions. Deep learning effectively transforms students from passive learners to critical thinkers who dare to ask questions. Conclusion: Deep learning in the Independent Curriculum received positive views from teachers and had a significant impact on student behavior at Rajapolah Elementary School.